A Novel Halotolerant Thermoalkaliphilic Esterase from Marine Bacterium Erythrobacter seohaensis SW-135 - Huo, Ying-Yi; Rong, Zhen; Jian, Shu-Ling; Xu, Cao-Di; Li, Jixi; Xu, Xue-Wei (Frontiers in Microbiology, 2017)
A novel esterase gene, e69, was cloned from Erythrobacter seohaensis SW135, which was isolated from a tidal flat sediment of the Yellow Sea in Korea. This gene is 825 bp in length and codes for a 29.54 kDa protein containing 274 amino acids. Phylogenetic analysis showed that E69 is a new member of the bacterial lipolytic enzyme family IV. This enzyme exhibited the highest level of activity toward p-nitrophenyl (NP) butyrate but little or no activity toward the other p-NP esters tested. The optimum temperature and pH of the catalytic activity of E69 were 60 °C and pH 10.5, respectively. The enzyme exhibited stable activity over a wide range of alkaline pH values (7.5–9.5). In addition, E69 was found to be a halotolerant esterase as it exhibited the highest hydrolytic activity in the presence of 0.5 M NaCl and was still active in the presence of 3 M NaCl. Moreover, it possessed some degree of tolerance to Triton X-100 and several organic solvents. Through homology modeling and comparison with other esterases, it was suggested that the absence of the CAP domain and its narrow substrate-binding pocket might be responsible for its narrow substrate specificity. Sequence and structural analysis results suggested that its high ratio of negatively to positively charged residues, large hydrophobic surface area, and negative electrostatic potential on the surface may be responsible for its alkaline adaptation. The results of this study provide insight into marine alkaliphilic esterases, and the unique properties of E69 make it a promising candidate as a biocatalyst for industrial applications.